2019
DOI: 10.1002/etc.4618
|View full text |Cite
|
Sign up to set email alerts
|

Source Identification and Health Risk Assessment of Polycyclic Aromatic Hydrocarbon‐Enriched PM2.5 in Tangshan, China

Abstract: Tangshan city in Hebei Province is one of the most heavily polluted cities in China, with substantial industrial emissions. The development of effective air pollution emission reduction policies requires knowledge of the sources and health risks of polycyclic aromatic hydrocarbon (PAH)-enriched fine particulate matter (PM 2.5 ). We investigated the seasonal variation and source apportionment of 16 priority PAH-enriched PM 2.5 samples in Tangshan during 2014 and 2015, and we assessed the health risks associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 43 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs), a significant class of toxic organic pollutants in the atmosphere (Masih et al, 2014;Tchórzewska-Cieślaka et al, 2017), are extremely easily adsorbed on fine atmospheric particles with small particle sizes and are found in high concentrations in the atmosphere (Ma et al, 2019), water (Fehmi et al, 2015), soil (Niu et al, 2020), crops (Oleszczuk and Baran, 2005), and food (Vichi et al, 2007), where they exhibit persistence, toxicity, and bioaccumulation. Since organic pollutants such as PAHs are associated with PM 2.5 in the air, their adverse effects on human health cannot be ignored, and they represent a significant health burden for Chinese citizens (Xu et al, 2015;Ying et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs), a significant class of toxic organic pollutants in the atmosphere (Masih et al, 2014;Tchórzewska-Cieślaka et al, 2017), are extremely easily adsorbed on fine atmospheric particles with small particle sizes and are found in high concentrations in the atmosphere (Ma et al, 2019), water (Fehmi et al, 2015), soil (Niu et al, 2020), crops (Oleszczuk and Baran, 2005), and food (Vichi et al, 2007), where they exhibit persistence, toxicity, and bioaccumulation. Since organic pollutants such as PAHs are associated with PM 2.5 in the air, their adverse effects on human health cannot be ignored, and they represent a significant health burden for Chinese citizens (Xu et al, 2015;Ying et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is widely recognized as a key topic in public health protection actions [1,2]. Exposure to particulate matter (PM) is one of the major global health concerns [3,4], since it may adversely affect human health, leading to the development of several chronic and acute pathologies, such as cardiovascular and respiratory diseases, lung cancer, bronchitis, diabetes, and neurodevelopmental disorders [5][6][7][8]. A growing number of epidemiological studies reported associations of PM pollution with health effects also at low levels, often below current air quality standards [9,10].…”
Section: Introductionmentioning
confidence: 99%